Kritik Nalar ‘irfa>ni Perspektif Muhammad Abed al-Jabiri - Fahmy Farid Purnama (Dialogia: Islamic Studies and Social Journal, 2016)
Abstract: 'Irfa>ni criticism is motivated by al-Jabri's anxiety that claims superiority intuition of human rationality. It means that 'Irfa>ni does not realize sense authority in the process of knowledge construction, to be questioned, and even sued. Al-Jabri assumes that 'Irfa>ni actually does not represent the highest reasoning models that are able to enrich truthful. Mystics claim that 'Irfa>ni is unreasonable because the level of its reasoning is higher than human brain. Furthermore, it could not be proven by scientific objectively, just imaginative intuition. Moreover, its reasoning is irrationality and consists of mythological elements and fantasy. In hence, 'Irfa>ni is the lowest rungs of Arabian Islamic epistemology which has lost its critical dimension.Keywords: Tura>th – ‘As}r al-Tadwi>n – al-Zama>n al-Tszqa>fi –la raison constituante (al-‘aql al-mukawwin) – la raison constituée (al-‘aql al-mukawwan) – al-‘Aql al-‘Irfa>ni